Mergers Among German Cooperative Banks: A Panel-based Stochastic Frontier Analysis - Günter Lang; Peter Welzel (Universität Augsburg, Institut für Volkswirtschaftslehre, 1997)
Based on an unbalanced panel of all Bavarian cooperative banks for the years of 1989-95 which includes information on 243 mergers, we analyze motives for and cost effects of small-scale mergers in German banking. Estimating a frontier cost function with a time-variable stochastic efficiency term we show that positive scale and scope effects from a merger arise only if the merged unit closes part of the former branch network. When we compare actual mergers to a simulation of hypothetical mergers, size effects of observed mergers turn out to be slightly more favorable than for all possible mergers. Banks taken over by others are less efficient than the average bank in the same size class, but exhibit on average the same efficiency as the acquiring firms. For the post-merger phase, our empirical results provide no evidence for efficiency gains from merging, but point instead to a leveling off of differences among the merging units.
urn:nbn:de:bvb:384-opus4-712752
Keywords: G21; L29; 330; banking; mergers; efficiency